2019
DOI: 10.1111/tpj.14288
|View full text |Cite
|
Sign up to set email alerts
|

A Nck‐associated protein 1‐like protein affects drought sensitivity by its involvement in leaf epidermal development and stomatal closure in rice

Abstract: SummaryWater deficit is a major environmental threat affecting crop yields worldwide. In this study, a drought stress‐sensitive mutant drought sensitive 8 (ds8) was identified in rice (Oryza sativa L.). The DS8 gene was cloned using a map‐based approach. Further analysis revealed that DS8 encoded a Nck‐associated protein 1 (NAP1)‐like protein, a component of the SCAR/WAVE complex, which played a vital role in actin filament nucleation activity. The mutant exhibited changes in leaf cuticle development. Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 87 publications
(110 reference statements)
0
19
0
Order By: Relevance
“…Several QTLs for dehydration tolerance and avoidance in rice were cloned via map-based cloning. Moreover, a large number of QTLs for root growth (Lou et al 2015), osmotic pressure regulation (Lilley et al 1996), ROS regulation, and cuticular wax accumulation which may contribute to enhance drought resistance were mapped to different locations of rice genome (Huang et al 2019;Huang et al 2009). DRO1, one of the gene that has been well-characterized, involves in the regulation of rice root development under drought stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several QTLs for dehydration tolerance and avoidance in rice were cloned via map-based cloning. Moreover, a large number of QTLs for root growth (Lou et al 2015), osmotic pressure regulation (Lilley et al 1996), ROS regulation, and cuticular wax accumulation which may contribute to enhance drought resistance were mapped to different locations of rice genome (Huang et al 2019;Huang et al 2009). DRO1, one of the gene that has been well-characterized, involves in the regulation of rice root development under drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…Loss function of DST increases stomatal closure, resulting in enhanced drought tolerance in rice (Huang et al 2009). In addition, DS8 participates in the synthesis of plant cuticular wax and in the regulation of stomatal movement in response to drought stress (Huang et al 2019). The studies of these genes indicated that intricate mechanisms are adopted in rice plants for the adaption of drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of QTLs for root growth [7], osmotic pressure regulation [8], ROS regulation, and cuticular wax accumulation, which contribute to enhanced drought resistance, have been mapped to different locations of the rice genome via map-based cloning [9][10][11]. DRO1, one of the genes that has been well characterized, is involved in the regulation of rice root development under drought stress.…”
mentioning
confidence: 99%
“…cuticular wax accumulation, which may contribute to enhanced drought resistance, have been mapped to different locations of the rice genome [9,10]. DRO1, one of the genes that has been well characterized, is involved in the regulation of rice root development under drought stress.…”
mentioning
confidence: 99%
“…Loss of DST function increases stomatal closure, resulting in enhanced drought tolerance in rice [10]. In addition, DS8 participates in the synthesis of plant cuticular wax and in the regulation of stomatal movement in response to drought stress [9]. Studies of these genes indicated that intricate mechanisms are employed by rice plants in the adaptation to drought stress.…”
mentioning
confidence: 99%